(untitled) (Journal of Building and Road Research, 2021)
The design of steel pipe piles in clay soils is faced with insufficient information regarding the parameters used for estimation of their static ultimate load capacity, namely the adhesion factor and plug length.This paper gives guides for the selection of the mentioned parameters. Direct shear and adhesion tests were performed. The soil tested is highly plastic silty clay statically compacted in the shear box at constant dry density and varying water content covering dry and wet of optimum water content. The adhesion factorwas computed for each test condition. An average value of 0.48 was found for the interface resistance when the water content is lower than the plastic limit. The factor was found to increase with increase in water content for water content higher than the plastic limit. The Plug length data was generated from a construction site in Melut Basin in Southern Sudanwhere steel pipe piles of different sizes were driven in very stiff to hard silty clay to about the same length and driving records were recorded with extra data regarding plug lengths. Geotechnical investigation preceded the construction activities. The plug data was analyzed for the effects of pile diameter and soil conditions on the plug length. Plug length to diameter ratio ranged between 3.8 and 8.0. Plug length increased linearly with increasing pile diameter and an excellent linear relationship was obtained between the average plug length for each diameter and pile diameter. Piles with small diameter gave lower resistance to penetration compared with those with larger diameters.